Growth Effects of non Proprietary Innovation - Gilles Saint-Paul (Center for Economic Studies and ifo Institute (CESifo), 2002)
We study an endogenous growth model where a profit-motivated R and D sector coexists with the introduction of free blueprints invented by philanthropists. These goods are priced at marginal cost, contrary to proprietary ones which are produced by a monopoly owned by the inventor. We show that philanthropy does not necessarily increase long-run growth and that it may even reduce welfare. The reason is that it crowds out proprietary innovation which on net may reduce total innovation in the long run. These effects would be reinforced if philanthropical innovation diverted people from other productive acitvities, if free goods were less tailored to customers than proprietary ones, and if philanthropical inventors sometimes came out with another version of an existing proprietary good. Dynamics can also be characterized and it is shown that the impact effect of free inventions on growth is positive.
Keywords: 330; innovation; R&D; growth; open source; philanthropy; monopoly; imperfect competition; software industry